Pertumbuhan Trichoderma sp. pada Beberapa Bahan Pembawa dan Kemampuannya Mengendalikan Penyakit Hawar Pelepah Padi - Sofi Kamilah Rahmatika; Satriyo Restu Adhi; Tatang Surjana (Universitas Respati Indonesia, 2026)
Sheath blight (Rhizoctonia solani) is an important disease of rice plants that can cause yield losses of up to 20% and will continue to increase if the severity is high. Excessive use of fungicides has a negative impact on living things and the environment. The solution that can be found is to utilize biological agents such as Trichoderma sp. to control plant diseases. The purpose of this study was to determine the effect of using several carrier materials on the growth of Trichoderma sp. and its ability to suppress rice sheath blight. This study used an experimental method with a Completely Randomized Design (CRD) Single Factor for the growth test of Trichoderma sp. on several carrier materials consisting of 4 treatments (B1, B2, B3, B4) and 6 replications, as well as a Single Factor Randomized Block Design (RBD) for the test of the ability of Trichoderma sp. to suppress sheath blight with 7 treatments (F0, F1, F2, F3, F4, F5, F6) and 4 replications. The results of the study showed that Treatment B4 (Parboiled Rice + Dry Chicken Manure + Sugar) produced the best growth of Trichoderma sp., and each Trichoderma sp. treatment had no significant effect on seed germination and the incidence of leaf sheath blight disease